Reading comprehension and strategy use: Comparing bilingual children to their monolingual peers and to bilingual adults - Friesen, Deanna C.; Schmidt, Katherine; Atwal, Taninder; Celebre, Angela (Frontiers in Psychology, 2022)
The current study investigated the predictive ability of language knowledge and reported strategy use on reading comprehension performance in English-speaking monolingual and bilingual students. 155 children in 4th through 6th grade (93 bilinguals and 62 monolinguals) were assessed on receptive vocabulary, word reading fluency, reading comprehension and reading strategy use in English. An additional 38 bilingual adults were assessed on the same measures. For both children groups, receptive vocabulary knowledge and word reading fluency predicted reading comprehension scores. For adults, only receptive vocabulary was a significant language predictor. For all groups, reported strategy use also accounted for unique variance in reading comprehension performance, but to different degrees, with more predictive ability observed in the bilingual groups. Findings highlight the strategies that successful readers report, suggest that bilinguals have greater need to rely on these strategies to experience reading comprehension success, and emphasize the value of promoting effective strategy selection in addition to language instruction in the development of reading comprehension skill.